Eksistensi Asas Accusatoir dalam Pembuktian Peradilan Pidana di Indonesia - Utami, Listy Fadilla; Lubis, Mhd Teguh Syuhada (Mahesa Research Center, 2024)
This study aims to explore how the existence of the accusatoir principle in proving criminal justice in Indonesia. This research uses normative juridical method by using primary data approach through library and statutory materials. The results of this study show that the legal study of the existence of the accusatoir principle in proving criminal justice in Indonesia based on indicators is as follows: First, the role of the accusatoir principle in proving criminal justice in Indonesia. Second, obstacles in the implementation of the accusatoir principle in proving criminal justice in Indonesia. Third, the existence of the accusatoir principle in proving criminal justice in Indonesia. The examination of the accused in the judicial process is a crucial stage that determines the direction and fairness in a case, it is also a major milestone in the criminal justice system that outlines the course of justice, provides an opportunity to listen, understand, and ensure the protection of the rights of individuals faced with due process. Research on the existence of accusatoir principles in the context of criminal justice evidence in Indonesia can make valuable contributions in several ways: legal system review, legal awareness raising, policy recommendations, and continuity of legal reform.